Aquatic Fungi from North Maharashtra-VII - Borse, B. D, S. Y. Patil and (Recent Research in Science and Technology, 2011)
Conidia of water-borne hyphomycetes are reported in foam samples collected from the river Tapti and Panzara of North Maharashtra. In all, five hyphomycetous taxa assignable to five genera were identified. The foam spora of North Maharashtra represents a mixture of both tropical and temperate fungi. Three species viz. Anguillospora crassa Ingold, Lunulospora curvula Ingold and Tetracladium marchalianum de Wildman are being reported for the first time from North Maharashtra region while two species viz. Campylospora filicladia Nawawi, Clavariopsis azalanii Nawawi, are being reported for the first time from Maharashtra State. Brief notes and illustration are given for each taxon. Geographical distribution of these fungi in India is also provided.